THE IMPLEMENTATION OF RESOLUTION 2728 IN UPHOLDING SEVERE HUMAN RIGHTS VIOLATIONS IN PALESTINE - Deu, Farhan; Puluhulawa, Mohamad Rusdiyanto U; Towadi, Mellisa; Rivera, Kevin M. (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to analyze the challenges in the implementation of UN Security Council Resolution 2728 in addressing serious human rights violations in Palestine, particularly in Gaza. The focus is to assess the effectiveness of the ceasefire and humanitarian aid access proposed in this resolution and to identify the key obstacles that have hindered its success in reducing violence against Palestinian civilians. Additionally, the study examines the role of the international community, especially the UN Security Council, in ensuring the resolution's implementation and monitoring of human rights violations. This research employs a qualitative approach, using literature analysis and secondary data, including official UN documents, humanitarian reports, and previous studies related to the implementation of Resolution 2728. The findings suggest that while Resolution 2728 provides a legal framework for addressing human rights violations in Palestine, its implementation has been obstructed by political and diplomatic challenges. Issues such as non-compliance with the ceasefire, restricted humanitarian access due to the Gaza blockade, and conflicting interests among UN Security Council member states, particularly the US's support for Israel, have significantly limited the resolution’s impact. Furthermore, the monitoring and accountability mechanisms for human rights violations have not been effectively enforced. This study gives contributions related to how to address political challenges and improve the implementation of Resolution 2728 in protecting human rights in Palestine.